Cover Feature: The Dual Effect of Coordinating −NH Groups and Light in the Electrochemical CO2 Reduction with Pyridylamino Co Complexes (ChemElectroChem 23/2021). Issue 23 (29th October 2021) - Fernández, Sergio; Cañellas, Santiago; Franco, Federico; Luis, Josep M.; Pericàs, Miquel À.; Lloret‐Fillol, Julio
Abstract : The Cover Feature illustrates the proposed mechanism for the electrocatalytic CO2 reduction to CO by the cobalt complex Co H, obtained by the combination of electrochemical, spectroscopic and theoretical studies, highlighting the CO labilization by blue light. Bringing light into the mechanism helped to improve the catalytic performance. More information can be found in the Article by S. Fernández et al .